Osteomyelitis due to methicillin-resistant Staphylococcus aureus successfully treated by an oral combination of minocycline and trimethoprim–sulfamethoxazole. (April 2019) - Sato, Kojiro; Yazawa, Hiroaki; Ikuma, Daisuke; Maruyama, Takashi; Kajiyama, Hiroshi; Mimura, Toshihide
Most of the anti-methicillin-resistant Staphylococcus aureus drugs available in Japan are administered intravenously, except for linezolid, which can also be administered orally. Here, we report a lupus patient with methicillin-resistant S. aureus– induced osteomyelitis. Linezolid had to be stopped due to severe anemia. In an effort to treat her on an outpatient basis, we planned to use a combination of minocycline and trimethoprim–sulfamethoxazole that exhibited in vitro sensitivity against the methicillin-resistant S. aureus detected, and rifampicin is used against methicillin-resistant S. aureus in certain cases. The use of rifampicin increased the level of C-reactive protein even though the prednisolone dose used was doubled, so we gave up using it. The combined application of oral minocycline and trimethoprim–sulfamethoxazole, however, controlled the inflammation, and the patient was able to be discharged. Fourteen months later, we discontinued the administration of both drugs and there has been no relapse more than a year. This combination of antibiotics may be useful, especially when patients want to be treated on an outpatient basis.